The role of nongovernmental organizations in primary education : a study of six NGOs in India - Jagannathan, Shanti, 1962- 1962- (Policy research working paper, 2001)
Nongovernmental organizations working in education in India are professional resource centers and innovators able to teach children who are educationally disadvantaged. The Indian government could improve the effectiveness of primary education by increasing its collaboration with such organizations